Pemanfaatan Blog Sebagai Media Pembelajaran Alternatif di Sekolah - Sartono Sartono (TRANSFORMATIKA, 2016)
This modern era is determined by the fast growing of information technology. It is also affected the education sector. Internet has become one alternative way for finding any kinds of information that the teacher and the students’ needs. There is no limited time and space for these kinds of technology. Teaching learning process becomes more flexible. Teacher and students could find themselves outside the classroom and regular time schedule. Moreover, students now are familiar with technology. They bring their gadget in a classroom. Sometimes, they use it for their own business when the teacher is explaining something. That is why the teacher must be creative to facilitate not only the demand for internet technology and also to increase the teaching learning process. Here, the writer proposes blog as one of the alternative media. The students can explore material that is posted by the teacher in the blog. Students can learn wherever and whenever, that of course it is really different with the conventional one.Keywords : education, technology, blog